Conceptual Consideration of the Verse of Examining Orphans “Vabtlu Al-yatama” about the Permissibility of the Intelligent Minor in Financial Possessions - Reza Haq Panah; Seyyed Ali Delbari (آموزه‌‌های فقه مدني, 2012)
Possessions and trading of the children are discussed both in jurisprudence of transactions and today’s law. In view of majority, this verse has mentioned the two characteristic of growth and maturity for delivering of property to the orphans and children; but there is disagreement among jurists and commentators that both of them must be accomplished or one of them will be adequate. Considering the opinions of jurists and commentators, it seems that the variable interference of the growth in trade of children, regardless of whether or not it coincides with the maturity, to be worthy of more serious reelection. Examining the mentioned verse in a descriptive-analytic way, this paper concludes that the element of growth is adequate for the permissibility of the intelligent minor in financial possessions.